Systems Thinking Safety Analysis: Nuclear Security Assessment of Physical Protection System in Nuclear Power Plants - Tae Ho Woo (Science and Technology of Nuclear Installations)
The dynamical assessment has been performed in the aspect of the nuclear power plants (NPPs) security. The physical protection system (PPS) is constructed by the cyber security evaluation tool (CSET) for the nuclear security assessment. The systems thinking algorithm is used for the quantifications by the Vensim software package. There is a period of 60 years which is the life time of NPPs' operation. The maximum possibility happens as 3.59 in the 30th year. The minimum value is done as 1.26 in the 55th year. The difference is about 2.85 times. The results of the case with time delay have shown that the maximum possibility of terror or sabotage incident happens as 447.42 in the 58th year and the minimum value happens as 89.77 in the 51st year. The difference is about 4.98 times. Hence, if the sabotage happens, the worst case is that the intruder can attack the target of the nuclear material in about one and a half hours. The general NPPs are modeled in the study and controlled by the systematic procedures.